WTO 11th Ministerial Conference – Buenos Aires: What’s at stake for domestic support in the context of agricultural negotiations - Illescas, Nelson; Jorge, Nicolás; Perini, Sofía C. (2017)
With the stagnation of the Doha Round, the WTO has started a process known as “early harvest”. The first results were achieved four years ago in Bali17, the process continued in Nairobi and is expected to have some outcomes in Buenos Aires, during the 11th Ministerial Conference of the WTO (MC11). In this context, the question is what to expect in Buenos Aires, especially in agriculture. The WTO Agreement on Agriculture includes rules for three pillars: Market Access (the use of trade restrictions, such as tariffs on imports), Export Competition (the use of export subsidies and other government support programmes that subsidize exports) and Domestic Support (the use of subsidies and other support programmes that directly stimulate production and distort trade). For the first one, given that it is a topic closely related to the non-agricultural negotiations (NAMA), it is going to be difficult to have results only in agriculture. The second one had some results during Nairobi, but nothing more until now. The last one is going to be the focus of this paper.